Pemeriksaan Golongan Darah Sistem ABO dan Sistem Rhesus di SMA Islam Al Syukro Universal Tangerang Selatan: Upaya Persiapan Sekolah Siaga Donor Darah - Sri Utami; Heny Kurniawati; Mutimanda Dwisatyadini; Diki Diki (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Blood type checking plays an important role in providing blood transfusion needs, and knowing one’s blood type is essential for every individual. However, most Indonesian do not know their blood type. The Blood Donor Alert School initiative in this community service program aims to establish a school where students are aware of, willing, and able to donate blood based on their blood type data. The implementation method includes conducting a survey to identify student characteristics, performing ABO dan rhesus blood type examinations, and documenting the data. The participants in this activity were 78 students from Al Syukro Universal High School, of whom more than half (56%) were unsure of their blood group. The results of the blood type test showed that 38% were blood type B, 21% were blood type O, followed by blood type A (6%) and AB (5%). All students were found to have a positive rhesus factor. Data on student characteristics and blood types were submitted to the school to support its readiness as a Blood Donor Alert School.